APPLICATION OF THE TEAM BASED PROJECT MODEL ASSISTED FLIPPED CLASSROOM IN SCIENTIFIC WRITING AT UNIVERSITY - Noni Febriana; Dian Anggraini (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Background : Higher Education Performance Indicators, the decision of the Minister of Education and culture number 754 / P / 2020 that there are two recommended learning methods, namely the Case learning method which reduces the Case based learning method and the Team Based Project which reduces the Project Based Learning method. Method : This research is motivated by the low writing skills of students and also the lack of strategies in teaching writing, especially writing scientific papers in the form of papers. Students have difficulty in using grammar, cohesion, coherence, paragraph organization, diction, and spelling errors. Result : The data and data sources in this study were students of the Department of Informatics Engineering Education, Faculty of Teacher Training and Education, Putra Indonesia University, Yptk Padang. The steps taken in this research are looking at the analysis of student needs, designing and implementing it in the learning process and evaluating the results of assignments. Conclusion : The findings in this research, students can conclude from the results that the application of the team based project model can improve students' abilities in writing scientific papers, especially papers